The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0001924000001743
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft flight characteristics in conditions of windshear and icing

Abstract: Complex weather conditions, especially windshear and icing encounter, have severe effects on aircraft flight safety. The effect of low-altitude windshear and ice accretion on aircraft performance and control has been studied in this paper. With the employment of a windshear model and nonlinear inverse dynamics (NID) method, a low-altitude windshear penetration flight control law is designed. The effect of ice accretion was modeled on the stability and control of an aircraft. Several icing parameters are import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The amplitude of the RMS tip displacement is dramatically reduced from 4.5 mm to 1.0 mm, exhibiting high gust alleviation efficacy for future practical applications. Cao et al proposed a low-altitude wind shear penetration flight control law using the Nonlinear Inverse Dynamics (NID) method (221,222) . The calculation results of an Airbus 300 aircraft indicated that the NID control logic works effectively in the aircraft trajectory control during the penetration of wind shear.…”
Section: Analytical Investigationsmentioning
confidence: 99%
“…The amplitude of the RMS tip displacement is dramatically reduced from 4.5 mm to 1.0 mm, exhibiting high gust alleviation efficacy for future practical applications. Cao et al proposed a low-altitude wind shear penetration flight control law using the Nonlinear Inverse Dynamics (NID) method (221,222) . The calculation results of an Airbus 300 aircraft indicated that the NID control logic works effectively in the aircraft trajectory control during the penetration of wind shear.…”
Section: Analytical Investigationsmentioning
confidence: 99%